Validation of the MediByte® Type 3 Portable Monitor Compared with Polysomnography for Screening of Obstructive Sleep Apnea - Helen S Driver; Effie J Pereira; Kathryn Bjerring; Fern Toop; Steven C Stewart; Peter W Munt; Michael F Fitzpatrick (Canadian Respiratory Journal)
BACKGROUND: Portable monitors are increasingly being used as a diagnostic screening tool for obstructive sleep apnea (OSA), and in-laboratory validation of these devices with polysomnography (PSG) is required.